CONTENT ANALYSIS ON TWO ENGLISH TEXTBOOKS FOR THE EIGHTH GRADER OF JUNIOR HIGH SCHOOL - Ary Setya Budhi Ningrum; Uum Midah Lestari; Nurul Retno Murti (Magister Scientiae, 2023)
This paper reports a study that analyzed the content of two English textbooks used in junior high school in Indonesia. The two textbooks are officially published by Indonesia's Ministry of Culture and Education. The first is "When English Rings a Bell," written by Siti Wachidah, Asep Gunawan, Diyantari, and Yuli Rulani Khatimah and published in 2017, and the second is "Modul Pembelajaran Jarak Jauh pada Masa Pandemi Covid-19 untuk jenjang SMP Mata Pelajaran Bahasa Inggris untuk semester genap kelas VIII” which is published in 2020. The findings revealed similarities and differences between the two textbooks. Two English textbooks differ greatly because they have different goals. The second book is not a revision of the first, but it appears to be the solution to the pandemic. The first textbook is designed to improve language skills through the use of communicative approach, both spoken and written, with English as the medium of communication. However, the second textbook is expected to be beneficial and meaningful for students to achieve the intended competence independently. Despite differences in goal or focus in developing the textbooks, they share similarities in terms of basic competence that students must achieve.